The Constructive Neutral Evolution of Behaviour - Andrew M. Catherall‐Ostler; Tanmay Dixit (Ecology and Evolution, 2025)
ABSTRACT There is an unrecognised disagreement between those studying molecular evolution and those studying behavioural evolution. Only natural selection is ordinarily thought to systematically increase behavioural complexity, but molecular biologists are increasingly recognising a second driver of complexity—constructive neutral evolution (CNE). CNE occurs when a system contains components that buffer the effects of otherwise‐deleterious mutations, allowing such mutations to spread. This increases the complexity of the system due to the dependency that now exists between the buffering component and the mutated component. A probabilistic ‘ratchet’ means this process is more likely to repeat itself than reverse, and hence complexity increases without necessarily any gain in function. Here, we argue that CNE operates not only at the molecular level, but also affects whole organism behaviour. We suggest that behaviour's polygenic architecture, flexibility, and ability to mitigate the impact of otherwise‐deleterious mutations mean that behaviour is particularly likely to evolve via CNE. We summarise the evidence that supports this hypothesis as well as suggesting how it could be tested further. We conclude that CNE must be considered alongside selective explanations for increases in behavioural complexity.